"Quando a liberdade passa pelo corpo" : o pensamento feminista e antifascista de Maria Teresa Horta (1968-1977) - Nascimento, Michelle Vasconcelos Oliveira do (2021)
The anti-fascist and feminist writer, journalist and activist Maria Teresa Horta (1937) was a staunch opponent of the Portuguese regime and conservatism, developing, over the years of the Portuguese dictatorship and in the democratization period, an intellectual production in Journalism and Literature areas. Her work, which must be understood as a whole, was at the heart of the denunciation of the repression and violence of the dictatorial government and the defense of freedom, especially for women, subjected to the regime's gender ideology, whose bodies were severely regulated and disciplined. This thesis aims to understand the development of Maria Teresa Horta anti-fascist and feminist thought during the final years of Salazarism and the beginning of democratization after the Revolução dos Cravos and following years, defending the thesis that her intellectual production constitutes a political activity essential for the study of the Political History of Portugal in the period. To achieve this goal, we chose the the period between 1968 and 1977, with the beginning of her work in the newspaper A Capital (1968) and the publication of Mulheres de Abril (1977), using different sources: journalistic, literary production, life history and judicial archives. Due to the sources diversity used and the complexity of the analyzed object, we use several methodological tools such as Discourse Analysis and Biographical Narrative. In addition, we make use of theoretical tools: Political History, Intellectual History and History of Women, in addition to knowledge of sister sciences such as Sociology, Philosophy and Literature. The research conduction and analysis of the sources showed us how Body and Freedom are the most highlight significants in the Hortian production of the period, constituting the basis of her intellectual thought and the anti-fascist and feminist struggle undertaken.